2018
DOI: 10.20892/j.issn.2095-3941.2017.0177
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 transarterial radioembolization versus conventional transarterial chemoembolization for patients with hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Objective:To compare the effects and safety of conventional transarterial chemoembolization (cTACE) and yttrium-90 transarterial radioembolization [TARE (90Y)] for hepatocellular carcinoma (HCC)Methods:Nine high-quality observational studies, one low bias-risk randomized controlled trial (RCT), and one moderate bias-risk RCT included 1,652 patients [cTACE, 1,124; TARE (90Y), 528], from whom data were extracted for this systematic review and meta-analysis.Results:The extracted study outcomes included 1-year and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 43 publications
(56 reference statements)
1
20
1
Order By: Relevance
“…Differing from other systematic reviews [ 8 , 31 33 ], our work examined both progression-free survival and time to progression, which are outcomes used as primary endpoints in some randomized controlled trials in HCC. Our results suggesting that the use of glass microsphere Y90-TARE may possibly be associated with longer time to progression as compared to standard of care treatment differ from prior meta-analyses [ 8 , 9 , 31 36 ]. Previous studies comparing the resin and glass microsphere to deliver the treatment showed conflicting results [ 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Differing from other systematic reviews [ 8 , 31 33 ], our work examined both progression-free survival and time to progression, which are outcomes used as primary endpoints in some randomized controlled trials in HCC. Our results suggesting that the use of glass microsphere Y90-TARE may possibly be associated with longer time to progression as compared to standard of care treatment differ from prior meta-analyses [ 8 , 9 , 31 36 ]. Previous studies comparing the resin and glass microsphere to deliver the treatment showed conflicting results [ 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Our work is however more exhaustive and not limited to one specific comparator in the context of absence of a unique standard of care. Previous systematic reviews suggesting a survival benefit with the use of Y90-TARE [ 9 , 35 , 36 ] had major limitations in their design including the consideration of non-randomised controlled studies. Differing from other systematic reviews [ 8 , 31 33 ], our work examined both progression-free survival and time to progression, which are outcomes used as primary endpoints in some randomized controlled trials in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including nine observational studies and 2 randomized trials ( n = 1652) found an association of Y-90 with higher OS, response rates and lower adverse event rates when compared to conventional TACE. Symptoms of post-embolization syndrome are less expected [50]. The first randomized phase II, with ( n = 28) Child–Pugh A patients identified similar disease control rates between the treatment strategies [51].…”
Section: Overview On the Current State Of Liver Directed Therapy Smentioning
confidence: 99%
“…No significant differences in the incidence of nausea and vomiting and fever have been observed, which is consistent with our study findings. To easily understand the research status of this subject, we summarized the meta studies in S6 Table [3,[45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%